Analysis of soft-sediment deformation structures in Neogene fluvio-lacustrine deposits of Caybagi Formation, Eastern Turkey - Tasgin, Calibe Koc; Turkmen, Ibrahim (Elsevier Science Bv, 2009)
During the Neogene, both strike-slip and extensional regimes coexisted in eastern Turkey and, a number of fault-bounded basins associated with the East Anatolian Fault System developed. The Caybagi Formation (Late Miocene-Early Pliocene) deposited in one of these basins consists of fluvio-lacustrine deposits. Numerous soft-sediment deformation structures are encountered in this formation, particularly in conglomerates, medium- to coarse-grained tuffaceous sandstones and claystones: folded structures (slumps, convolute laminations, and simple recumbent folds), water-escape structures (intruded sands, internal cusps, interpenetrative cusps and sand volcanoes), and load structures (load casts, pseudonodules, flame structures, and pillow structures). These structures are produced by liquefaction and/or fluidization of the unconsolidated sediments during a seismic shock. Consequently, the existence of seismically-induced deformation structures in the aybagi Formation and the association with a Neogene intraformational unconformity, growth faults, and reverse faults in the aybagi basin attest to the tectonic activity in this area during the Late Miocene and Early Pliocene. The East Anatolian Fault System, in particular the Uluova fault zone, is the most probable seismogenic source. Earthquakes with a magnitude of over 5 in the Richter scale can be postulated. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Caybagi Formation; Seismites; Liquefaction; Fluidization; East Anatolian Fault System